The CO‐City: Sharing, Collaborating, Cooperating, and Commoning in the City. (March 2016) - Iaione, Christian
Abstract: This article introduces an innovative, experimental, adaptive, and iterative approach to creating legal and institutional frameworks based on urban polycentric governance to foster commons‐based urban policies. First, the theory of urban/local governance is introduced, based on an urban co‐governance matrix. A new type of regulatory system is then described that aims at transforming people in distributed nodes of collective action. Citizens and institutions can be myriad nodes of designing and problem solving in the public interest. Urban co‐governance aims at taking advantage of this galaxy of networks. I then examine design principles and a methodology to implement the urban co‐governance matrix. The concluding question concerns the need for a new research methodology to investigate the ongoing process of state transformation and institutional genesis at the urban level.